Value Pluralism in Ian McEwan’s Black Dogs and Saturday - Nešić, Marija B. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
Ian McEwan, an influential and provocative British novelist and short-story writer, has addressed a variety of issues, distinguishing himself as a socially and politically engaged author. This paper explores contemporary liberalism as depicted in two of McEwan’s novels, Black Dogs and Saturday, both charged with moral complexity. The analysis is approached from the perspective of value pluralism, which recognises the plurality of morally correct yet incompatible and incommensurable principles or values. These values may conflict with each other, but since all are correct, the conflicts remain unresolved. It is the author’s belief that the novels highlight value pluralism through characters who, while navigating a pluralist environment, disclose the challenges and limitations of liberal democracies. The theoretical context this paper relies on is based on ideas of Isaiah Berlin and his notion of value pluralism.